Addressing the Advertising of Controversial Products in China: An Empirical Approach - Fam, Kim-Shyan (Journal of business ethics, 2009)
China is a country that has undertaken a great transformation since the late 1970’s, and among these changes, has seen a massive growth in the advertising industry with the influx of foreign advertisers, and the development of regional and global media, such as satellite television and the Internet. This has resulted in the Chinese people of all ages having a greater opportunity of exposure to different types of advertising, including the advertising of potentially controversial products, which could clash with traditional Chinese values. Using a stakeholder theory approach, this study analyzes the responses of 630 Chinese respondents to discover who is offended by controversial advertisements and determine ways potentially offensive advertising messages can be reduced, thereby assisting marketers in being more socially responsible in their advertising messages.